Penanganan Laporan Pengaduan Masyarakat terhadap Proses Penyidikan Polri di Tingkat Polres dan Polsek - Mochammad Sochib; Setiyono Setiyono; Indrawati Indrawati (MLJ Merdeka Law Journal, 2020)
The purpose of the study was to analyze the handling of public complaint reports that could not be handled properly with the police investigation process and the regulation of the National Police Chief regarding the handling of reports of public complaints against the police investigation process at the level of Polres and Polsek in the future. The problem approach used is normative juridical supported by empirical juridical. The data used are primary data. Analysis Techniques used in normative legal research. The results of the study indicate that officers of the Polres supervision section are expected to be able to serve well every community complaint and be thorough in the investigation process of the National Police at the Polres and Polsek levels. The need for a change in the organizational structure of the Polres supervision section with the addition of a section specifically handling community complaints in the Polres Supervision Sub Section so that it does not overlap with other work.DOI: https://doi.org/10.26905/mlj.v1i1.4292.